Determinants of net interest margin on commercial bank in United States / Nur Raidah Syafiqah Abdul Razak - Abdul Razak, Nur Raidah Syafiqah (2018)
This paper provides study on Determinants of Net Interest Margin in commercial banks in United States over the period of 2006 until 2017. The purpose of this paper is to examine and investigate the main drivers of bank's net interest rate margins across selected commercial banks throughout the United States. Also, the study explored the relationship between the dependent variable, net interest margin (NIM) and a set of selected banks specific variables by employing panel data estimation methodology. In line with some expectations, findings of this paper will confirm the importance of net interest margin as net interest margin is the most suitable criterion in evaluating the stability and also efficiency of bank's operations. In this study found that the total loan total deposit (TLTD) and operating expenses to total asset (OETA) as positively influencing factors while total loan to total asset (TLTA) and common equity to total asset (CETA) has no significant influence on net interest margin (NIM). This in turn shows that liquidity and efficiency hold an important criterion to ensure optimal net interest margin (NIM) in banks.